Bibliometric analysis of papers on mild cognitive impairment nursing in China - Yating Ai; Kaili Sun; Hui Hu (Elsevier, 2017)
Purpose: To supply further references by analyzing the status of research on mild cognitive impairment nursing in China. Methods: Papers on mild cognitive impairment nursing published between 2005 and 2014 were collected from China National Knowledge Infrastructure, Wanfang Data, and China Biological Medicine database, while their publication dates, journals, and types were subjected to a bibliometric analysis using NoteExpress and Excel. Results: A total of 68 papers were collected from the selected databases. The number of papers on mild cognitive impairment nursing increased annually. The selected papers were published in 44 journals, 55.88% of them were published in core journals, 35.29% received funding support, 35.29% were published by hospitals affiliated to colleges, 47.06% were published by other local hospitals, author collaboration is 2.66, and 66.18% showed co-authorship. These papers covered a wide range of topics, but were only conducted based on clinical interventions. Around 29.41% of these papers had a citation frequency of over 5, the highest citation frequency was 29, and the highest h-index was 23. Conclusion: Beijing and Shanghai established core author groups for mild cognitive impairment nursing research. These studies should focus on the community and psychological nursing of such impairment. Targeted nursing interventions on different types of mild cognitive impairment should be adopted, new avenues for research should be opened, and various research methods should be introduced. Keywords: Mild cognitive impairment, Nursing, Bibliometric